The Effect of Variation of Types of Microbial Starters on The Physical Characteristics of Modified Cassava Flour (MOCAF) Rich in Beta-Carotene - Alfansuri, Habib Ra'uf; Fatoni, Rois; Fathoni, Ahmad; Setiarto, R. Haryo Bimo; Damayanti, Ema (Universitas Sebelas Maret (UNS), 2023)
The development of beta-carotene-rich mocaf flour as a functional food aims to increase its nutritional content and functional properties as an antioxidant for health. The development of beta-carotene-rich mocaf flour can be optimized through good fermentation methods, especially with the use of starter. This study aims to further analyze the effect of using a type of starter on the mocaf characteristics of cassava species rich in beta-carotene through a comparison of several types of starter. In this study, three types of starter were used, namely the Bimo-CF starter, the Berhasil starter and thse BRIN starter. The results showed that the use of starter during fermentation affected the physicochemical properties of mocaf flour in the form of differences in solubility, increased viscosity and decreased syneresis. Scanning Electron Microscope (SEM) was used to analyze the microstrutural of mocaf flour using starter during fermentation resulted in a more massive reshuffling of starch granules and causes changes in the structure of starch granules that become irregular round in shape with increasingly non-uniform sizes. NIR (Near infrared) and proximate analysis of the content of mocaf flour, showed that the use of the Bimo-CF starter, the Berhasil starter and the BRIN starter during fermentation affected the decrease in moisture content, protein content, ash content, fiber content, phosphorus, and increased fat and dry matter content.